Perbedaan Kualitas Hidup antara Lansia Wanita yang Berpasangan dengan Tidak Berpasangan di Posyandu Lansia Kecamatan Sumbersari Kabupaten Jember - Iken Nafikadini; Nurul Hikmah Ramadani; Husni Abdul Gani (Jurnal Kesehatan, 2021)
Quality of Life is a concept affected in a complex way by the person's physical health, psychological state, social relationships, and their relationship to salient features of their environment. This research aimed to determine the difference in the quality of life between the married and single elderly woman in posyandu for elderly Sumbersari Subdistrict, Jember Regency. This research was analytically studies using cross sectional design. The number of sample was 140 respondent selected by multistage random sampling. Mann Whitney and Kruskal Wallis test (alpha 0,05) was applied to analyze the data. There were not significant difference between quality of life of the married and single elderly woman (p=0,498). Good quality of life was greater in elderly women in pairs of 16.4%. There were a significant differences in elderly women who were had couples and who did not in pairs quality of life with the physical domain (p = 0,000), social relations (p = 0,000) and the environment (p = 0.001). Keywords:  Quality of Life. Married and Single Elderly Woman, Posyandu for Elderly